Manifestaciones de conducta disruptiva y comportamiento perturbador en población normal de 4 a 17 años de edad - Arias Correa, Grace (Editorial Bonaventuriana, 2019)
This current paper shows the results of a research whose aim was to identify highprobability cases showing externalizing behaviors in the normal population, a crosssection study was designed with a sample of 444 participants, who were given the SNAPIV (Swanson, Nolan & Pelham, 1983). The results showed differences in the Information provided by each one of the sources (parents and teachers) as well as the presence of behaviors with high-risk probability, which may be intervened in the school or family setting